If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 2) + -3(x + -1) = 30 Reorder the terms: 6(2 + x) + -3(x + -1) = 30 (2 * 6 + x * 6) + -3(x + -1) = 30 (12 + 6x) + -3(x + -1) = 30 Reorder the terms: 12 + 6x + -3(-1 + x) = 30 12 + 6x + (-1 * -3 + x * -3) = 30 12 + 6x + (3 + -3x) = 30 Reorder the terms: 12 + 3 + 6x + -3x = 30 Combine like terms: 12 + 3 = 15 15 + 6x + -3x = 30 Combine like terms: 6x + -3x = 3x 15 + 3x = 30 Solving 15 + 3x = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 3x = 30 + -15 Combine like terms: 15 + -15 = 0 0 + 3x = 30 + -15 3x = 30 + -15 Combine like terms: 30 + -15 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| -1.8j+3.9=-3.3 | | -x-(13+14x)=-3(5-9x)+2 | | -4r-56=-11+9(12r-5) | | 15+9m=-3(-6m+7) | | -3=-3h+4 | | 3.7=-.21w | | 20x^2-3x-2=0 | | -(8-6n)=60-7n | | a^2+36+13a=0 | | 21+9x=11+2(-10+7x) | | (x-5)(x-5)-81=0 | | 3x^2+8=-16 | | -2.6t-3.4=-0.8 | | -3u+12=0 | | -5=13-6x | | 0.2z+0.7=1.5 | | 5n+3=z(n+2)-3n | | 4(11p-6)=-56+12p | | 14-5x=-8(x-4)-6x | | 23=7times+3times+3 | | -7v+26=0 | | -3(2x-4)+7x=13 | | 14-5x=-8(x-4)-7x | | -2(-8v-1)=18v | | 3x^2-5x-1=0 | | -2u+9=-8 | | (w+5)(w-9)=0 | | 4(-6c-18)=2(12+4c) | | -7(n+4)=-35-6n | | 0=5u+15 | | 2s^2+17s+35=0 | | 8-4x=5x+8 |